A Report on Metal Forming Technology Transfer from Expert to Industry for Improving Production Efficiency - Khoirudin Khoirudin; Sukarman Sukarman; Murtalim Murtalim; Fathan Mubina Dewadi; Nana Rahdiana; Amin Rais; Amri Abdulah; Choirul Anwar; Aries Abbas (Mechanical Engineering for Society and Industry, 2021)
This article reports on technological mastery assistance in three small metal forming industries in Indonesia. Problems in the blangking and piercing separately process caused increased production time which resulted in inefficiency cost. Therefore, the expert team aided in metal forming technology through participatory action research (PAR) methods and experimental methods through reverse engineering for several products. The PAR method involves optimal contribution and participation from the industry. Assistance in mastering technology in small metal-forming industries reduces the manufacturing process from seven to three stages, increasing efficiency. The press machine's tonnage capacity must balance with the force blanking/piercing requirement. The minimum press machine requirement is 6.7 tons, and based on the availability of existing press machines, the expert team recommends a 20-ton capacity press machine. Total efficiency can be further increased by implementing full progressive die technology by combining piercing, blanking, and bending processes.